Modern principles of physical rehabilitation of patients with Osteochondrosis of the cervical-thoracic spine - Borys Pustovoit (Kharkiv State Academy of Physical Culture, 2018)
Presents the results of the use of physical rehabilitation program (therapy) patients with Osteochondrosis of the cervical-thoracic spine. Purpose: to research and develop and substantiate, evaluate the effectiveness of program for the physical rehabilitation of patients with Osteochondrosis of the cervical-thoracic spine. Materials & Methods: medical-biological, instrumental, hardware, medical-pedagogical observation, evaluation of motor function, conducting trials and tests methods of mathematical statistics. Results: the study posited clinico-functional examination of 57 patients with Osteochondrosis of the cervical-thoracic spine, which conducted rehabilitation using the diagnostic-therapeutic training apparatus "David". Conclusions: the use of physical therapy program, which included a complex of mechanotherapy (developed on software DavidSpineConcept) and classic massage, contributed to the positive dynamics of clinical manifestations of the disease, the normalization of the State of the cardiovascular system.